Analysis of Russian Arctic LNG projects and their development prospects. Issue 1 (September 2020) - Merkulov, V I
Abstract: This article provides a detailed description of the Yamal LNG project, including a general description of the project, supply geography, project infrastructure including port, airport and settlement of Sabetta as wll as resource base of the project and LNG transportation routes. Opportunity of the new North-South transport corridor for LNG transportation is considered. The issues of gasification of the Arctic zone of Russia using LNG were also studied including LNG transportation facilities, shore storage systems, floating gas storage and floating power plants. Strategic analysis of Russian Arctic LNG projects was carried out. Conclusions have been made on the localization of production of critical equipment for LNG production as well as the opportunities of export of Russian gas liquefaction technology to world markets. Also the localization of shipbuilding for the needs of Arctic LNG projects, the diversification of LNG sales routes, the use of LNG as a transport fuel and the gasification of a number of Russian regions using the LNG logistics infrastructure were offered.